2001
DOI: 10.1093/oxfordjournals.jbchem.a002860
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Emerin and Nuclear Lamins

Abstract: Emerin is an inner nuclear membrane protein that is involved in X-linked recessive Emery-Dreifuss muscular dystrophy (X-EDMD). Although the function of this protein is still unknown, we revealed that C-terminus transmembrane domain-truncated emerin (amino acid 1-225) binds to lamin A with higher affinity than lamin C. Screening for the emerin binding protein and immunoprecipitation analysis showed that lamin A binds to emerin specifically. We also used the yeast two-hybrid system to clarify that this interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(90 citation statements)
references
References 0 publications
5
83
0
2
Order By: Relevance
“…EDMD is also caused by mutations in the gene encoding emerin, a LEM domain protein (Bione et al, 1994;Manilal et al, 1996;Nagano et al, 1996). Emerin interacts with A-type lamins (Clements et al, 2000;Sakaki et al, 2001) and is mislocalized in many patients with LMNA mutations (Ben-Harush et al, 2009;Muchir et al, 2003;Sullivan et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…EDMD is also caused by mutations in the gene encoding emerin, a LEM domain protein (Bione et al, 1994;Manilal et al, 1996;Nagano et al, 1996). Emerin interacts with A-type lamins (Clements et al, 2000;Sakaki et al, 2001) and is mislocalized in many patients with LMNA mutations (Ben-Harush et al, 2009;Muchir et al, 2003;Sullivan et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Protein fragments can easily be used as bait since they don't have to be incorporated in vivo, and have been applied to describe interactions between the specific domains of the nuclear envelope proteins otefin, lamin A, nesprin. 45,49,50 The benefit of choosing the exact bait composition can further be exploited by choosing domains involved in disease mechanisms, like the 50 amino acid deleted region in progerin, shown in a Y2H screen to interact with the NURD chromatin remodeling complex component Rbbp4. 6 Disadvantages of Y2H assays are the lack of information on protein complex composition, the inability to study posttranslational modifications and the large amount of false positives identified.…”
Section: Novel Interactors Identified By Msmentioning
confidence: 99%
“…After blocking with PBS containing 2% BSA and 5% heatinactivated normal goat serum, the sections were incubated with primary antibodies for 2 hours at 37°C. Primary antibodies used in this study are: rabbit anti-phospho-A-type lamin polyclonal antibodies at 1:50; mouse anti-human merosin (M-chain) monoclonal antibody (5H2) (Chemicon International, Temecula, CA) at 1:400; rabbit anti-lamin A polyclonal antibody (Sakaki et al, 2001) at 1:400; mouse anti-Pax7 monoclonal antibody (Developmental Studies Hybridoma Bank, Iowa City, IA) at 1:300. Sections were incubated with anti-rabbit IgG antibody conjugated with AlexaFluor-488 and anti-mouse IgG antibody conjugated with Alexa-Fluor-568 (Invitrogen, Carlsbad, CA) at 1:500 for 45 minutes at room temperature.…”
Section: Immunohistochemistrymentioning
confidence: 99%